BRAND ASSOCIATION ATTRIBUTES FOR INDONESIAN NATIONAL AIRLINE - Idris Gautama So; Ishak Ismail (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2009)
Brand image, in brief is a series of private values that perceived by company to create identity of its product or service. Brand Association is anything related memory to brand (Tjiptono, 2005). Brand Association is one of assets of brand equity, which shows advantages and differences of a product or service while a person recall the brand of product or service. This paper is a research to discover brand attributes associated in consumers’ mind that create brand image of state owned national airline (Garuda Indonesia-GI), and then to discover harmonization between brand identity with brand image. The respondents of this research are passengers of GI airline at Sukamo-Hatta airport. Cochran test is one of methods applied in this paper. The result of this research shows that there are six brand associations which create GI brand image, but brand identity has not yet stuck completely in consumer’s mind, although there are three additional brand image perceived by consumers. These show that there is a positive gap which bring advantages to company. Company must also maintain the harmony of built brand image and brand identity to avoid the creation of negative gap.